The Effect of Receiving Local Tax on Regional Original Income in Surabaya City - Setyawati, Vincentia Devina; Putri, Johana Raycia (EAJ (Economic and Accounting Journal), 2023)
Street Lighting Tax (PPJ), Land and Building Tax (PBB), and Land and Building Title Transfer Duty (BPHTB) are types of local taxes whose income is more significant than other taxes. This research aims to determine the influence of receiving PPJ, PBB, and BPHTB on original regional income in Surabaya City. The population used in this research is the report on the realization of PPJ, PBB, BPHTB, and original regional income in Surabaya City from 2013-2020. The data used in this research are quarterly, so the sample used is as much as 32 quarters. The data analysis technique used a model test, multiple linear regression analysis, coefficient of determination, and t-test. Based on the research results, it can be obtained that PPJ has a significant impact on original regional income, and PBB has a significant impact on original regional income. In contrast, BPHTB has no significant impact on original regional income. Regional governments must periodically disseminate BPHTB payments to increase public awareness of paying taxes.